Isolation and molecular characterization of circulating extracellular vesicles from blood of chronic Chagas disease patients. (31st March 2022) - Madeira, Rafael P.; Meneghetti, Paula; de Barros, Lucas A.; de Cassia Buck, Paula; Mady, Charles; Ianni, Barbara M.; Fernandez‐Becerra, Carmen; Torrecilhas, Ana C.
Abstract: Extracellular vesicles (EVs) are lipid bilayer envelopes that encase several types of molecules. Their contents mostly reflect their cell origin and possible targets at other locations in the organism and can be modified in pathological conditions to interfere with intercellular communication, thus promoting disease establishment and development. These characteristics, in addition to their presence in virtually all body fluids, make such vesicles ideal for biomarker discovery in human diseases. Here, we describe the effect of different anticoagulants and the combination of two purification methods for isolation and characterization of circulating EVs from blood of chronic Chagas disease (CCD) patients. We illustrated this procedure by studying a population of patients with Chagas disease at the indeterminate chronic stage, in which the Trypanosoma cruzi is very scarce in circulation. EVs were harvested from blood collected without or with different anticoagulants. Protein and nanoparticle tracking analysis was used to measure EVs size and concentration. The EVs were purified by ultracentrifugation, followed by size‐exclusion chromatography and characterized by chemiluminescent enzyme‐linked immunosorbent assay and dot blot using antibodies that recognized parasite‐derived EVs, such as hyperimmune sera, polyclonal and monoclonal antibodies against trans ‐sialidase and mucins. In parallel, antibodies against classical human EV markers CD9, CD63, CD81, and CD82, were also analyzed. The results showed that anticoagulants did not interfere with the analyzed parameters and circulating EVs from CCD patients contain T. cruzi antigens and classical human exosomal markers. Overall, our protocol is adequate for the isolation of the total circulating EVs and can serve as an important basis for further studies on biomarker discovery in Chagas' disease.